ANALISIS POTENSI SUMBER DAYA ALAM (SDA) DI WISATA SELONDO DESA NGRAYUDAN, KECAMATAN JOGOROGO, KABUPATEN NGAWI - Risdeanita, Devita Eka; Agnafia, Desi Nuzul; Muttaqin, Sabiqul; Mayantika, Bq Ulfa; Mustika, Aulia (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2025)
Background: Natural resources always involve various interests, including the interests of the state, investors, society, and also the environment itself. In Ngawi, Selondo Tourism has enormous natural resource potential. This potential includes enormous natural resources. This potential includes resources that can be developed, such as plants and plantations, as well as those that cannot be developed, such as sand and stone. Methods: Qualitative descriptive methods were used through observation, interviews with local residents, and literature review. Results: Key recommendations include community-based planning, infrastructure development, and environmental education. Using this strategy, the Selondo area can develop as a tourist destination that supports environmental preservation and community welfare.